COMMENTS OF PHILIP S. SCHAENMAN, PRESIDENT, TRIDATA, FOR THE FIRE-SAFE CIGARETTE TECHNICAL STUDY GROUP MEETING, 870910 - 870911 - SCHAENMAN,PS (Tufts Archival Research Center, 2007)
Speech by Philip Schaenman, President of the TriData Corporation to the Study Group on fire safe cigarettes claiming that the amount of cigarette started fires may be miscalculated and problem of this type of fire is exaggerated. Includes suggestions to make the data more accurate and reader friendly.